Analysis of Investment Risk and Return - Muchdi Alwi; Muhammad Ali; Fauzi R Rahim (Magister Management, Hasanuddin University, 2022)
This study aims to determine the level of risk and return on shares obtained by PT. Jiwasraya during the 2017-2020 period using the CAPM method. The sample used is purposive sampling based on certain criteria, namely the troubled shares owned PT. Jiwasraya for the 2017-2020 period. The results of this study indicate that 2 of the 24 shares were risky (β > 1) like SIMA shares with beta (1,981777) and PCAR with beta (16,323271), which means this stock is an aggressive stock. There are 23 out of 24 stocks that provide a return below the expected return such as the BNBR stock return, namely (0) with an expected return (0,00387) which means that the return obtained by PT. Jiwasraya is not as expected.